(untitled) (Discussion Papers, 2012)
This paper has been prepared for the presentation of the research results of the project titled ‘Urban Areas, Socio-spatial Inequalities and Conflicts - The Socio-spatial Factors of European Competitiveness’. The project’s basic research tasks were as follows: to analyse the socio-spatial inequalities manifesting in social conflicts in the metropolitan regions of Hungary and to prepare a comparative analysis of the socio-spatial inequalities and conflicts in the metropolitan areas of Hungary and Central Europe. The investigation of the major social factors of the competitiveness of urban areas was another key target of basic research. On the basis of primary research results a research concept has been prepared on the practical implementation of research objectives i.e. reducing socio-spatial inequalities in urban areas, finding solutions for the management of local social conflicts, improving the socio-economic competitiveness of urban areas. The present paper is a summary of the major research results of the problem of social inequalities in metropolitan areas. As a basic theoretical study illustrated by case studies from Hungary, Austria and the Czech Republic, it provides a general summary of our findings.